PENYELESAIAN SENGKETA MELALUI SMALL CLAIM COURT - Sari, Septi Wulan (IAIN Tulungagung, 2016)
Small Claims Court is a court which is informal, simple and low-cost,has the force of law, and is intended to provide a quick and economicalsolution to resolve disputes which does not require an expensive cost.This research is a Library Research or literature review that includes:the systematic identification, analysis of documents containinginformation related to the problems of the study. The approach used inthis study is normative juridical approach. In the developed countrieswhich follow SCC Systems Common Law and Civil Law systems, suchapproach has become one of the alternatives that are used in thehandling of cases in the state. In Indonesia the problem of the SmallClaims Court is described in PERMA No. 2/2015.Kata kunci: Penyelesaian Sengketa, Sengketa Sederhana, SmallClaim Court